(untitled) (Research, Society and Development, 2022)
Purpose: To compare the effect of intramuscular administration of dexamethasone versus Traumeel S® on patients’ oral health-related quality of life (OHRQoL) after surgical extraction of impacted lower third molars (3M). Patients and methods: A randomized, triple-blinded clinical trial was conducted. The sample was composed of 17 patients with asymptomatic bilateral lower 3M positioned as class IIB according to the Pell and Gregory classification. The patients were randomly assigned into 2 groups: intramuscular dexamethasone or Traumeel S®. The OHRQoL was assessed using the Oral Health Impact Profile (OHIP) version 14. It was considered patients’ perception regarding different quality of life dimensions, in the first seven postoperative days. Results: There was a significant OHRQoL improvement in the dexamethasone group when compared to Traumeel S® group. It was noted a significant decrease of psychological disability and psychological discomfort in patients receiving dexamethasone vs those receiving Traumeel S®. Conclusion: Intramasseteric injection of dexamethasone showed a greater improvement of the OHRQoL following 3M surgeries when compared to Traumeel S® injection.